Evaluation of Red and Green Colored Bell peppers for the Production of Polyclonal IgM and IgG Antibodies in Murine Spleen Cells - Sarker, Md Moklesur Rahman (Bangladesh Pharmaceutical Journal, 2021)
Immunostimulants are greatly required for the upregulation of immunity to fight against viral and bacterial infections and cancers. Bell peppers (Capsicum annuum L.), eaten as vegetables, are rich sources of vitamin C and E, provitamin A, β-carotene, and numerous phenolic compounds. Antimicrobial, antioxidant, anti-mutagenic and anti-inflammatory properties of Bell peppers were reported. Our research group for the first time reported the immunomodulatory activities of Bell peppers. In this study, we evaluated the antibody production abilities of two different colored Bell peppers (red and green) in the culture of antibody producing splenic B cells of mice. Antibodies and the number of viable cells were determined by an ELISA and MTT assays, respectively. Red Bell pepper Extract (RBPE) at the doses of (0.375, 0.75, 1.5, and 2.25 mg/mL) significantly augmented the production of polyclonal IgM and IgG antibodies in-vitro. The highest amount of IgM antibody production was observed by the dose of 1.5 mg/kg which was 3 times higher than that of the untreated cells. Similarly, RBPE also enhanced the production of IgG antibody in the culture of murine splenic B cells. On the contrary, cultural treatment of murine splenic B cells with Green Bell pepper Extract (GBPE) could not stimulate the B cells, and hence, failed to produce neither IgM nor IgG antibody. Thus the current findings suggest that consumption of Red Bell Pepper extract or its vegetables, not green pepper, may be beneficial to strengthen humoral immune responses. Bangladesh Pharmaceutical Journal 24(1): 45-53, 2021